Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Non-destructive detection for early-stage blueberry bruise via spectral reshaping and dynamic attention-driven deep learning - Yuping Huang; Zhouchen Bian; Khurram Yousaf; Xuzhong Cao; Haojun Jin; Dong Hu; Ye Sun; Weijun Xie; Chenlong Fan (Postharvest Biology and Technology, 2026)

Intelligent compost maturity assessment: A hybrid computer vision and physicochemical parameters - Haojun Xie; Xueru Zhu; Chao Li; Fan Jiao; Xuebin Feng; Yiyun Zhang; Hua Li (Sustainable Chemistry and Pharmacy, 2026)

A ultralong-life and high-capacity Mg/Na hybrid-ion battery using four-leaf clover-shaped CuSe2/(Cu, Co)Se2 cathode pairing with triglyme electrolyte - Ting Zhou; Tianli Han; Fengming Ma; Cheng Wang; Yunmiao Fan; Xuehui Wang; Haojun Xu; Jiawei Long; Jinjin Li; Huigang Zhang; Jinyun Liu (Chemical Engineering Journal, 2026)

Porous solvent-free polyurethane coating with 3D conductive network for efficient electrothermal/photothermal conversion and intelligent temperature sensing - Qiang Gao; Weiwei Fan; Zhonghui Wang; Haojun Fan; Jun Xiang (Chemical Engineering Journal, 2026)

Photothermal hydrogel triggered erythrocyte fuel combustion strategy for rapid hemostasis in lethal non-compressible hemorrhage - Lizong Tang; Jiameng Li; Xinran Yang; Duo Li; Yanjiao Teng; Yuchen Zhang; Zhiguang Sun; Xiaoqin Guo; Yanqing Liu; Shike Hou; Haojun Fan; Jie Shi; et al. (Chemical Engineering Journal, 2026)

Engineering inhaled nanocarriers for ALI/ARDS: From pathological microenvironment deconstruction to integrated theranostic co-delivery platforms - Jie Jin; Fenshuang Zheng; Qianying Lu; Yiting Yin; Dejin Yang; Yingyi Zhang; Yangfan Liang; Chuanchuan Liu; Yanmei Zhao; Haojun Fan (Chemical Engineering Journal, 2025)

Crystal structure-dependent ammonium-ion storage mechanisms in nanostructured MnO2 polymorphs - Jingang Wu; Binbin Wei; Quanxing Guo; Haojun Zeng; Xin Liu; Qiaoyan Chen; Xutao Yan; Yuechan Li; Qi-Yuan Fan; Zhengbing Qi; Hanfeng Liang (Chemical Engineering Journal, 2025)

A compact on-chip microsensor for dual-channel measurement of potassium and creatinine in whole blood - Haijing Tian; Ruo Wu; Qi Lv; Jie Shi; Xiaoqin Guo; Duo Li; Chunli Liu; Qi Li; Weijia Zheng; Haojun Fan; Xuexin Duan; Qiannan Xue (Analytica Chimica Acta, 2025)

Lactobacillus rhamnosus GG Regulates Host IFN-I Through the RIG-I Signalling Pathway to Inhibit Herpes Simplex Virus Type 2 Infection - Jingyu Wang; Mei Huang; Yuqi Du; Haoming Chen; Zixiong Li; Taiyu Zhai; Zihao Ou; Yiyi Huang; Fan Bu; Haojun Zhen; Ruoru Pan; Yubing Wang; et al. (Probiotics and Antimicrobial Proteins, 2024)
Numerous recent studies have demonstrated that the commensal microbiota plays an important role in host immunity against infections. During the infection process, viruses can exhibit substantial and close interactions with the commensal microbiota. However, the associated mechanism remains largely unknown. Therefore, in this study, we explored the specific mechanisms by which the commensal microbiota modulates host immunity against viral infections. We found that the expression levels of type I interferon (IFN-I) and antiviral priming were significantly downregulated following the depletion of the commensal microbiota due to treatment with broad-spectrum antibiotics (ABX). In addition, we confirmed a unique molecular mechanism underlying the induction of IFN-I mediated by the commensal microbiota. In vivo and in vitro experiments confirmed that Lactobacillus rhamnosus GG (LGG) can suppress herpes simplex virus type 2 (HSV-2) infection by inducing IFN-I expression via the retinoic acid-inducible gene-I (RIG-I) signalling pathway. Therefore, the commensal microbiota-induced production of IFN-I provides a potential therapeutic approach to combat viral infections. Altogether, understanding the complexity and the molecular aspects linking the commensal microbiota to health will help provide the basis for novel therapies already being developed. Graphical Abstract

Urban flooding damage prediction in matrix scenarios of extreme rainfall using a convolutional neural network - Mo Wang; Haowen Fan; Haojun Yuan; Dongqing Zhang; Jin Su; Shiqi Zhou; Qifei Zhang; Jianjun Li (Journal of Hydrology, 2024)

Corrigendum to ‘Boosting organics degradation via sulfite activation by Fe/Mn@CF composite electrode: Performance and mechanism’ [Chem. Eng. 493 (2024) 152342] - Ertai Zhang; Shuyan Guan; Haojun Fan; Yongxin Wang; Hui Yan; Lei Guo; Xuedong Zhai; Carlos A. Martínez Huitle; Jing Ding (Chemical Engineering Journal, 2024)

Boosting organics degradation via sulfite activation by Fe/Mn@CF composite electrode: Performance and mechanism - Ertai Zhang; Shuyan Guan; Haojun Fan; Yongxin Wang; Hui Yan; Lei Guo; Xuedong Zhai; Carlos A. Martínez Huitle; Jing Ding (Chemical Engineering Journal, 2024)

Identification and validation of a novel necroptosis-related molecular signature to evaluate prognosis and immune features in breast cancer - Fan Zhang; Chenxue Qi; Zhipeng Yao; Haojun Xu; Guoren Zhou; Congzhu Li; Hongping Xia (Apoptosis, 2023)

Exposure levels and possible health effects of HAP on rural housewives in northwest China - Yamin Huang; Yushan Huang; Huiling Wang; Jinping Fan; Xiangli Li; Chengyun Li; Haojun Zhang; Junling Wang (Toxicology and Environmental Health Sciences, 2023)

Determination of total catechins in tea extracts by HPLC and spectrophotometry - Qiang He; Kai Yao; Dongying Jia; Haojun Fan; Xuepin Liao; Bi Shi (Natural Product Research, 2009)